Prehospital pain management in mass casualty scenarios: a scoping review - Morris, Christopher (Division of Emergency Medicine, 2026)
Background: Effective pain management in mass casualty scenarios (MCS) is critical due to the high prevalence of severe pain and its association with increased morbidity. MCS, defined as incidents where patient care needs exceed available resources, pose unique challenges for prehospital care providers. This scoping review aims to synthesize existing evidence on prehospital pain management strategies, identify gaps, and inform future research and policy development. Methods: Following PRISMA-ScR guidelines, a comprehensive literature search was conducted across major medical databases (PubMed/MEDLINE, EMBASE, CINAHL, Scopus, and Web of Science) and grey literature repositories, covering studies published from 2005 to 2024. Inclusion criteria encompassed English-language studies addressing prehospital pain management in MCS, reporting on pain assessment, pharmacological/non-pharmacological interventions, or resource limitations. Excluded were hospital-based studies and non-evidence-based publications. Data were charted and synthesized into thematic categories. Results: The review included 22 studies, highlighting significant gaps in standardised pain management protocols and documentation. Key findings revealed underutilisation of analgesics, with only 3.2% of MCS cases receiving pain medication. Ketamine and regional anaesthesia emerged as viable options, particularly in resource-limited settings, while novel delivery systems like autoinjectors showed promise. Major barriers included resource shortages, provider training gaps, and limited integration of pain management in triage systems. Conclusion: Prehospital pain management in MCS requires scalable, evidence-based protocols emphasising early analgesic administration, particularly ketamine and multimodal strategies. Systemic barriers, including inadequate training and documentation, hinder effective implementation. Addressing these gaps through improved training, simplified protocols, and better resource planning can enhance patient outcomes and disaster response capabilities. Future research should prioritise paediatric care and standardised outcome measures to further refine pain management in diverse MCS contexts.